Feasibility and performance investigation of a new smart system integrating planar/tubular thermoelectric generators with solar flat plate collector. (1st November 2019) - Faddouli, A.; Labrim, H.; Fadili, S.; Hartiti, B.; Habchi, A.; Ertugrul, M.; Cavusoglu, B.; Ntsoenzok, E.
Highlights: A novel solar thermal/planar/tubular thermoelectric hybrid system is proposed. The effect of the cooling system on the TEG performance is analyzed. The performances of this new system under real concentrated sunlight are presented. The smart system cogenerating the heat and electricity simultaneously. This design improves the storage operation by the automatic variation in flow rate. Abstract: A model of a tri-generation unit consisting of solar water heater collector, integrated with tubular and planar thermoelectric generators (TEGs) is presented. In order to optimize and obtain the effects of solar irradiance and solar concentration on the performance of system, a set of functions were coded in the MATLAB software. Twelve nonlinear algebraic equations were derived for the mathematical model and solved via the Finite Difference Method. The thermal and electrical efficiencies, the electrical characteristics of the thermoelectric, the thermal and electrical power of the hybrid device were analyzed in this study. The results have reflected some improvements on the thermal efficiency by placing tubular TEG inside the lateral area of the absorber tube and planar TEG between the absorber and cooler plates. In order to validate the results of the mathematical model, each device studied separately to evaluate the obtained results, which are in good agreement with the results in the literature. Furthermore, the use of a concentrator shows the significant improvements in model temperatures, especially the working fluid that exceeds 100 °C, for which a developed program is established to control the flow rate in order to keep the temperature at 60 °C. This approach shows an excellent effect on the storage operation. Therefore, for a concentration of 20 suns, the thermal efficiency reached to 86.5% with benefit of electrical power about 161.68 Watts and quantity of hot water up to 1345 L/day, which is very promising for future solar thermal/electrical developments.